Hubungan Current Ratio, Struktur Modal, dan Ukuran Perusahaan terhadap Kinerja Keuangan Perusahaan Pertambangan yang Terdaftar di BEI Periode 2014-2016 - Hartoyo Hartoyo (Universitas Proklamasi 45 Yogyakarta, 2018)
This study aims to find out and to analyze the Current Ratio, Capital Structure, and Corporate Size partially affect the Financial Performance of Mining Companies listed on the Indonesian Stock Exchange (BEI) in the period 2014-2016. The sample used is 120 financial statements of mining companies listed in BEI. The method used in sampling is purposive sampling. Data is collected by downloading, recording, researching, and copying information relating to the issues discussed in the study. Data analysis using descriptive statistics, classical assumption test, and multiple linear regression analysis, t-test, and coefficient of determination (R2). The results of this study indicate that current ratio and the size of the company does not affect on financial performance of mining companies on BEI in the 2014-2016, while the capital structure has a significant effect on the financial performance of mining companies on the company’s financial performance.